2018
DOI: 10.1039/c8tc03855d
|View full text |Cite
|
Sign up to set email alerts
|

Designing lead-free bismuth ferrite-based ceramics learning from relaxor ferroelectric behavior for simultaneous high energy density and efficiency under low electric field

Abstract: The strategy of constructing weakly coupled polar structures is feasible and effective to boost the energy density and efficiency for bismuth ferrite-based bulk ceramics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 234 publications
(80 citation statements)
references
References 41 publications
2
75
0
Order By: Relevance
“…In detail, increasing temperature produces the emergence of more field-induced long-range polar phase owing to the increase of thermal activation energy, [94,95] thus yielding the increase of P max . On the other hand, field-induced polar structures becomes more unstable in thermodynamics as increasing temperature, [96,97] generating the appearance of lower P r at high temperature. As a consequence, one can find that increasing temperature results in the enhancement of energy-storage performance, as shown in Figure 6d.…”
Section: Resultsmentioning
confidence: 99%
“…In detail, increasing temperature produces the emergence of more field-induced long-range polar phase owing to the increase of thermal activation energy, [94,95] thus yielding the increase of P max . On the other hand, field-induced polar structures becomes more unstable in thermodynamics as increasing temperature, [96,97] generating the appearance of lower P r at high temperature. As a consequence, one can find that increasing temperature results in the enhancement of energy-storage performance, as shown in Figure 6d.…”
Section: Resultsmentioning
confidence: 99%
“…The obvious changes of P-E loops conrm that the long-range ferroelectric order of BNKT ceramics has been disrupted into ergodic relaxor (ER) phase. 26 As the Nb content further increases to 7%, the critical electric eld for the phase transition between relaxor and ferroelectric increases sharply, evidenced by the quasi-linear loops with relatively low P m . Fig.…”
Section: Energy Storage Propertiesmentioning
confidence: 97%
“…The inherent ferroelectric order exists stably even when the electric eld is withdrawn, manifested in the large P r . On increasing the Nb content to 3%, four current peaks (P 1 , P 2 , P 3 , P 4 ) appear, 6,26 it's reported that these four current peaks are related to the ER phase induced by the Nb content modifying. The ER phase would transform into metastable ferroelectric phase under exerted electric eld, corresponding to P 1 /P 3 current peaks, resulting in large P m. When removing the electric eld, the induced long-range order would change back to the initial ER state, corresponding to P 2 /P 4 current peaks, resulting in the low P r .…”
Section: Energy Storage Propertiesmentioning
confidence: 99%
“…On the other hand, in relaxors, the polarization decreases until P r approaches values close to zero at E = 0 [ 78 ]. Hence, to achieve high ED properties, the difference between P s and P r , otherwise written as P s -P r has to be maximized [ 79 ] by minimizing the energy dissipations (dielectric losses) in material (c.f. Figure 2 )—in other words obtaining a slim hysteresis loop.…”
Section: Tuning Energy Density By Chemical Substitutionmentioning
confidence: 99%
“…Figure 2 ) possesses a small P s -P r value, making it not suitable for energy storage applications because of the resulting low J r . Chemical substitutions in the lattice introduce local disorder and random fields that disrupt the long-range polar order so that no well-developed FE domains exist but only short-range localized polar entities [ 79 ]. Moreover, HeV substitutions can also introduce defects such as vacancies as charge compensation schemes that restrict the domain wall movement by the ‘pinning effect’, resulting in lower mechanical losses upon field reversal.…”
Section: Tuning Energy Density By Chemical Substitutionmentioning
confidence: 99%